Characterization of Oil Palm Shell Activated Carbon and ZSM-5 Supported Cobalt Catalysts - Izirwan, Izhab; Mohd, Asmadi; Nor Aishah, Saidina Amin (2013)
In this paper we are reporting the preparation and characterization of supported cobalt catalysts using a wetness impregnation method. Different cobalt catalysts loading of 0 and 10 wt% were prepared by dissolving cobalt nitrate hexahydrate in distilled water and dried in an oven at 100 °C overnight. Two selected supports of oil palm shell (OPS) activated carbon and ZSM-5 zeolite were employed and compared. Catalysts characterizations of both supports were performed by thermogravimetric analysis (TGA), X-ray diffraction (XRD) analysis and scanning electron microscope analysis (SEM). Using Scherrer equation, the cobalt metallic size was calculated. OPS activated carbon supports were further analyzed for CHNOS elemental analysis. Both supports of OPS activated carbon and ZSM-5 zeolite exhibited the successful loading of cobalt catalysts and have potential to be utilized in catalytic reactions.